METODOLOGI PENAFSIRAN KONTEKSTUAL ABAD 21: : Tawaran Tafsir Alquran Abdullah Saeed - zainuddin fanani; Juliansyah (LP3M IAI Al-Qolam, 2019)
The reconstruction effort on interpretation continues to be carried out with various methods and approaches. This reflection then causes various Muslim and non-Muslim intellectuals to compete in interpreting Al-Qur'anic text. The purpose of this research is to find out Abdullah Saeed's contextual interpretation methodology in Al-Qur'an 21st Century. This research uses the book of Abdullah Saeed's entitled